INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) AND FINANCIAL PERFORMANCE OF SELECTED MONEY DEPOSIT BANKS IN NIGERIA - Babatunde, Dorcas Adebola (Annals of Spiru Haret University. Economic Series, 2022)
This study examined International Financial Reporting Standards (IFRS) and financial performance of selected money deposit banks in Nigeria. Specifically the study analyzed the effect of adoption of IFRS on profit after tax (PAT), return on asset (ROA) and return on equity (ROE) of 10 randomly deposit money banks over the period of 14 years covering Pre-IFRS and IFRS era. Data used for the study were collected from the financial statements of the selected banks. Panel estimation techniques including pooled OLS, fixed effect and random effect estimation were employed, after which the most consistent and efficient estimation result was evaluated using restricted F-test and Hausman test. Result showed that adoption of international financial reporting standards has positive effect on all the measures of performance, starting from profit after tax, return on asset and return on equity with reported coefficient estimate of 24.8241(p < 0.05) for PAT model; 3.566556(p > 0.05) for ROA model and 232.5723(p > 0.05) for ROE model respectively. This study established that adoption of international financial reporting standard explain a notable percentage of systematic variation in the performance of deposit money banks especially when measured in terms of profit after tax, and concluded that adoption of international best practices of reporting (IFRS) promoted improved performance of firms in Nigeria banking industry view from the perspectives of profitability as well as return on investment of asset and equity. Hence, regulatory authorities in Nigeria banking industries should devise a mechanism for evaluation consistency of deposit money banks as torching adherence to international standards of reporting. Management and auditors of accounting report need to work together at tightening compliance to ensure better performance impact of IFRS adoption. Also, Financial Reporting Council of Nigeria should further harmonize their operation in the bit to sustain proper check and balances needed to ensure coherence in the regulatory framework necessary for proper adoption of IFRS in the country